2022
DOI: 10.1126/science.abi9547
|View full text |Cite
|
Sign up to set email alerts
|

Zonated leucine sensing by Sestrin-mTORC1 in the liver controls the response to dietary leucine

Abstract: The mechanistic target of rapamycin complex 1 (mTORC1) kinase controls growth in response to nutrients, including the amino acid leucine. In cultured cells, mTORC1 senses leucine through the leucine-binding Sestrin proteins, but the physiological functions and distribution of Sestrin-mediated leucine sensing in mammals are unknown. We find that mice lacking Sestrin1 and Sestrin2 cannot inhibit mTORC1 upon dietary leucine deprivation and suffer a rapid loss of white adipose tissue (WAT) and muscle. The WAT loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…A key effector of leucine is believed to activate the mTORC1 protein kinase (Cangelosi et al, 2022). In our study, inhibiting mTORC1 was found to suppress Arg1 expression and inhibit leucine-mediated M2 polarization (Figure 4A and Supplement Figure 3A).…”
Section: Mtorc1 Mediates Leucine Induced M2 Polarizationmentioning
confidence: 51%
“…A key effector of leucine is believed to activate the mTORC1 protein kinase (Cangelosi et al, 2022). In our study, inhibiting mTORC1 was found to suppress Arg1 expression and inhibit leucine-mediated M2 polarization (Figure 4A and Supplement Figure 3A).…”
Section: Mtorc1 Mediates Leucine Induced M2 Polarizationmentioning
confidence: 51%
“…The complex cellular response observed upon glutamine starvation suggests a complementary regulation of mTORC1 through several pathways [ 43 ]. In contrast, direct leucine sensing of Sestrin2 could be a reason for a more selective Sestrin2-dependent inhibition of mTORC1 for this branch of amino acid utilization/metabolism [ 21 , 44 , 45 ]. Glutamine deprivation causes leucine accumulation in glutamine-deprived pancreatic cancer cells [ 35 ], which could disrupt the Sestrin2:GATOR2 complex important for Sestrin2-dependent mTORC1 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Free leucine can bind to Sestrin1/2, causing their conformational changes, which leads to the dissociation of GATOR2 (GAP activity towards Rags complex 2). [80][81][82] GATOR2 is now able to F I G U R E 2 LAT1-4F2hc in mTORC1 signalling and the intergraded stress response. Cartoon showing components of the nutrientsensing as well as growth factor sensing pathway upstream of mTORC1.…”
Section: The Importance Of Lat1-4f2hc In Mtorc1 Signallingmentioning
confidence: 99%
“…Among those, the essential amino acid leucine is particularly important to activate mTORC1. Free leucine can bind to Sestrin1/2, causing their conformational changes, which leads to the dissociation of GATOR2 (GAP activity towards Rags complex 2) 80–82 . GATOR2 is now able to inhibit GATOR1, a conserved GAP (GTPase‐activating protein) for Rag A/B.…”
Section: Lat1–4f2hc Is a Key Regulator In Cellular Growthmentioning
confidence: 99%